Imagining future digital assistants at work: A study of task management needs - Khaokaew, Yonchanok; Holcombe-James, Indigo; Rahaman, Mohammad Saiedur; Liono, Jonathan; Trippas, Johanne R.; Spina, Damiano; Bailey, Peter; Belkin, Nicholas J.; Bennett, Paul; Ren, Yongli; Sanderson, Mark; Scholer, Falk; et al. (International Journal of Human-Computer Studies, 2022)
Digital Assistants (DAs) can support workers in the workplace and beyond. However, target user needs are not fully understood, and the functions that workers would ideally want a DA to support require further study. A richer understanding of worker needs could help inform the design of future DAs. We investigate user needs of future workplace DAs using data from a user study of 40 workers over a four-week period. Our qualitative analysis confirms existing research and generates new insight on the role of DAs in managing people’s time, tasks, and information. Placing these insights in relation to quantitative analysis of self-reported task data, we highlight how different occupation roles require DAs to take varied approaches to these domains and the effect of task characteristics on the imagined features. Our findings have implications for the design of future DAs in work settings and we offer some recommendations for reduction to practice.